462 USE OF QUANTITATIVE INSULIN SENSITIVITY CHECK INDEX (QUICKI) IN THE SCREENING OF HYPERINSULINEMIA IN OVERWEIGHT CHILDREN AND ADOLESCENTS. (1st January 2006) - Mayman, G. A.; Evans, W. N.; Acherman, R. J.; Kip, K. T.; Cass, K. A.; Luna, C.F; Rothman, A.; Gustafson, A.; Lowe, A.; Restrepo, H.
Abstract : Background: Obesity in children and adolescents is a risk factor for development of type 2 diabetes later in life. Early detection of hyperinsulinemia with a simple but reliable clinical test is highly desirable. Objective: To evaluate the Quantitative Insulin Sensitivity Check Index (QUICKI) as a screening tool for hyperinsulinemia in a group of non-diabetic overweight children and adolescents in a clinical setting. Methods: This study included 598 children and adolescents with a body mass index (BMI) ≥ 95% percentile, referred to our risk factor reduction program for nutrition and healthy habits counseling. Fasting blood samples, for determination of glucose and insulin levels, were obtained early in the morning, during the first visit to the program. QUICKI was calculate as follows: 1/(log [insulin mIU/L] + log [glucose mg/dL]). The receiver operating characteristic (ROC) curve was constructed using the upper value of the normal range for clinical laboratory values of insulin (17 mIU/L). T test and binary nominal correlation was used for statistical analysis. Results: There were 358 boys and 240 girls, mean age: 10.7 years (range: 2-18), mean BMI Z-score: 2.52 ± 0.58, ethnic distribution: Hispanic: 50%, Caucasian: 33%, African American: 11% and other races: 6%. Area under ROC curve was 99% (95% confident interval: 0.987-0.999). The best cutoff value of QUICKI for diagnosis of hyperinsulinemia was 0.317, sensitivity: 97.7%, specificity: 93.0%, positive likelihood ratio: 14.04. Those patients with a QUICKI ≤ 0.317 had statistically significant higher mean fasting insulin serum values than those with a QUICKI > 0.317 (31.8 ± 15.9 vs 10.8 ± 4.4 mIU/L, p < .001). Clinical diagnosis of hyperinsulinemia was highly correlated with hyperinsulinemia diagnosed by QUICKI (Phi coefficient correlation: 0.27, p < .0001). Conclusions: In this group of overweight children and adolescents QUICKI showed a high correlation with the clinical diagnosis of hyperinsulinemia. At a cutoff value of ≤ 0.317 in this group of subjects the index had high predictive diagnostic values.